2013
DOI: 10.1007/s12639-013-0382-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of toxoplasmosis on the level of some sex hormones in males blood donors in Baghdad

Abstract: Toxoplasma gondii is a unique intracellular parasite, which infect a large proportion of the world population, but uncommonly causes clinically significant disease. The present study was performed to estimate the prevalence of toxoplasmosis in 400 apparently healthy blood donor males, their ages were between 18 and 57 years using enzyme linked immunosorbent assay, and to examine the effects of infection on total testosterone, free testosterone and follicle stimulating hormone (FSH) levels in their sera. Seropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
(19 reference statements)
0
17
1
Order By: Relevance
“…This is a cross-sectional study regarding the seroprevalence and molecular evaluation of T. gondii infection among healthy blood donors of Boyer-Ahmad County in southwest Iran. The overall seroprevalence of 16.8% for toxoplasmosis in the current study indicates a considerable rate of toxoplasmosis in the population, but the seroprevalence rate of toxoplasmosis in our study is lower than the rates reported in blood donors from most of the areas in Iran [ 2 , 7 , 25 ] and other regions as reported from Turkey (22.59%) [ 26 ], Czech Republic (34.23%) [ 27 ], Brazil (60%) [ 28 ], Saudi Arabia (40%) [ 29 ], Iraq (32.75%) [ 30 ], Egypt (59.6%) [ 31 ], and India (53.7%) [ 32 ]. Variations in the rate of seropositivity of T. gondii in different regions of the world or in different areas of a given country can be attributed to the differences in climate, topographical conditions, and food behavior.…”
Section: Discussioncontrasting
confidence: 70%
“…This is a cross-sectional study regarding the seroprevalence and molecular evaluation of T. gondii infection among healthy blood donors of Boyer-Ahmad County in southwest Iran. The overall seroprevalence of 16.8% for toxoplasmosis in the current study indicates a considerable rate of toxoplasmosis in the population, but the seroprevalence rate of toxoplasmosis in our study is lower than the rates reported in blood donors from most of the areas in Iran [ 2 , 7 , 25 ] and other regions as reported from Turkey (22.59%) [ 26 ], Czech Republic (34.23%) [ 27 ], Brazil (60%) [ 28 ], Saudi Arabia (40%) [ 29 ], Iraq (32.75%) [ 30 ], Egypt (59.6%) [ 31 ], and India (53.7%) [ 32 ]. Variations in the rate of seropositivity of T. gondii in different regions of the world or in different areas of a given country can be attributed to the differences in climate, topographical conditions, and food behavior.…”
Section: Discussioncontrasting
confidence: 70%
“…In addition, some mechanisms suggesting a possible relation between T. gondii and ADHD are as follows: (a) The T. gondii genome is known to contain two aromatic amino acid hydroxylases potentially capable of directly affecting dopamine and/or serotonin biosynthesis [6]. (b) The ability of Toxoplasma cysts to produce damage by settling in the brain and, additionally, to cause changes in the dopaminergic and neurotransmitter systems suggests that Toxoplasma may be involved in the etiology and severity of ADHD and (c) Higher testosterone levels have been determined in men with latent toxoplasmosis compared to controls [35,36]. Testosterone has been shown to be linked to dopamine release [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…An effect of latent toxoplasmosis on serum testosterone changes is still being discussed by researchers. Published data have shown increased and decreased testosterone levels associated with T. gondii seropositivity in humans [ 17 19 ]. In the current study, effects of latent toxoplasmosis on serum testosterone were assessed in men and women.…”
Section: Introductionmentioning
confidence: 99%